Self-medication practices and associated factors among pregnant women in Oromia, Ethiopia: institutional based cross-sectional study - Ahmed, Hadra Nuri; Damtew, Beyene Sisay; Bezabih, Wondu Abera; Wakwoya, Elias Bekele; Abdi, Hinsermu Bayu; Tiruye, Getahun (Frontiers in Medicine, 2025)
BackgroundSelf-medication, the practice of using medications without medical prescription, is a widespread phenomenon, particularly among pregnant women. This practice can lead to serious adverse effects on both the mother and the fetus, including drug interactions, birth defects, and premature labor. Despite its potential risks, the prevalence and factors associated with self-medication during pregnancy in Ethiopia remain understudied.ObjectiveThis study aimed to assess the prevalence of self-medication practices and identify the factors associated with it among pregnant women attending antenatal care in Oromia, Ethiopia.MethodsA cross-sectional study was conducted from August to September 2023, involving 418 pregnant women attending antenatal care at public health institutions in Asella. A structured questionnaire given by an interviewer was used to gather data. Using SPSS version 25, the gathered data was cleaned, coded, and examined. Binary logistic regression analysis was used to determine the factors associated to self-medication, and descriptive statistics were used to summarize the data.ResultsOverall the prevalence of self-medication practice among pregnant women was 39.5% (95%CI: 34.7–44.7%). Factors associated with self medication practice during pregnancy are; Primigravida women (AOR 2.18, 95% CI: 1.08–3.38), those with unintended pregnancies (AOR 1.65, 95% CI: 1.20–1.70), lacking health education on self-medication during (AOR 1.50, 95% CI: 1.45–2.55), those previous pregnancy and delivery related problem (AOR 1.6, 95% CI 1.55–2.65) were significantly associated with self-medication practice.Conclusion and recommendationSelf-medication is a prevalent practice among pregnant women in Asella, Ethiopia. To mitigate the risks associated with self-medication, it is crucial to implement comprehensive health education programs targeting pregnant women, particularly primigravida women and those with unintended pregnancies. These programs should emphasize the dangers of self-medication, the importance of seeking professional medical advice, and the proper use of medications during pregnancy.